The image of the German in current literature and media - Liutkevičienė, Danutė (Verbum, 2021)
The aim of this article was to analyse the reflection of the image of the German in the examples from the current literature and the media present in the Corpus of the Contemporary Lithuanian Language of the Vytautas Magnus University. The focus of the study went beyond the collocations with this word and the disclosure of the characteristic traits of Germans all the way to the meaning bestowed upon this word by the broader context – the sentence or a group of them. Examples containing all forms of the lexeme German were examined. A total of six different contexts in which Germans are mentioned were identified: these were the contexts of history, cooperation, sports, culture, characteristic traits, and science.In the context of history, Germans are usually referred to as a belligerent nation, assailants, savage conquerors, invaders. The attitude towards them is negative as often as not. Things are different in the context of cooperation, where the attitude is positive and Germans are seen as friendly partners. In the contexts of sports, culture, and science, the story is more or less the same, with Germans regarded with respect as meritorious and high-ranking representatives of their field.The context of the characteristic traits of Germans has the highest degree of controversy and stereotype. Some data show that Germans, according to the popular belief, are neat, rational, organised, punctual, disciplined, hard-working, cultured, law-abiding; they are rather cold and reserved. Other examples, albeit much smaller in number, bear witness to quite the opposite: that Germans are neither punctual nor overly neat or cultured; some sources even say that they are friendly, merry, and approachable. Besides, this nature loves to travel.
Keywords: corpus; context; semantics; meaning; illustrative example; German